Seamless QoS-Enabled Handover Scheme Using CoMP in Fast Moving Vehicular Networks - Sunghun Chae; Tuan Nguyen; Yeong Min Jang (International Journal of Distributed Sensor Networks)
Vehicular networks create new opportunities to develop innovative and enhanced solutions for generating reliable communication among vehicles. To widely deploy vehicular networks, it is needed to overcome several existing research challenges in such networks. Guaranteeing data transmission is one of the main challenges in vehicular networks that are specified by their large scale and high mobility. Recently, the effective deployment of femtocell networks inside high speed moving vehicles, in order to improve the quality of data transmission, is an interesting topic for researchers. In this paper, we propose a novel handover scheme utilizing coordinated multiple point transmission (CoMP) in high speed moving vehicular femtocell networks. The proposed scheme aims at a seamless, deployable, and efficient handover procedure for this specific environment. We take into account signal-to-interference-plus-noise ratio (SINR) and outage probability to evaluate the performance of our proposed handover scheme.